The Conversion of Jacob Reihing: Academic Controversy and the Professorial Ideal in Confessional Germany. Issue 1 (30th December 2017) - Kirwan, Richard
Abstract: This article examines the case of the controversial seventeenth-century theologian Jacob Reihing. In 1621 Reihing fled Pfalz-Neuburg, where he had played an instrumental role in re-Catholicizing the territory, to seek asylum in Württemberg. His defection provoked shock and dismay in political, religious and academic circles in Pfalz-Neuburg and Bavaria. In Stuttgart Reihing was granted the protection of the duke and sent to the University of Tübingen. Jesuits and Catholic princes made a series of interventions, first in an effort to encourage Reihing to return to the fold and then to blacken his name. In spite of these pressures, the endorsements of the duke of Württemberg continued apace: Reihing was allowed a very public ceremony of conversion and was appointed professor of theology in Tübingen. The task of rehabilitating the former Jesuit fell largely to the University of Tübingen. Its professors attempted to refashion Reihing as an archetypal Lutheran scholar and carefully tended his public image over the remaining years of his life. For their part the Jesuits intensified their attempts at character assassination. The battle over Reihing's reputation continued until and, indeed, beyond his death. This article explores the controversies generated by Reihing's conversion and subsequent life and career and examines in particular the struggle over his reputation. In doing so it addresses a wider clash of ideals governing academic identities, lifestyles and behaviours in which scholars and institutions divided by confession participated.